The practice of and reflection on problem-based learning in academic postgraduate clinical medicine education - Ya-Fei ZHANG; Hui-Fang CHEN; Ning LUO; Wen-Li YU; Qiu ZHAO (Yixue xinzhi zazhi)
Problem-based learning has been widely employed in medical education in Western countries, which plays an important role in promoting students' skill to analyze and solve problems, as well as independent learning. In this article, we combine our own practical experience to discuss, the application of problem-based learning in clinical medicine education among academic postgraduate.